2021
DOI: 10.3390/vaccines9020085
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines: Antigen Selection Strategy

Abstract: Unlike traditional cancer therapies, cancer vaccines (CVs) harness a high specificity of the host’s immunity to kill tumor cells. CVs can train and bolster the patient’s immune system to recognize and eliminate malignant cells by enhancing immune cells’ identification of antigens expressed on cancer cells. Various features of antigens like immunogenicity and avidity influence the efficacy of CVs. Therefore, the choice and application of antigens play a critical role in establishing and developing CVs. Tumor-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 178 publications
0
24
0
Order By: Relevance
“…Antigens can be tumor-specific antigens (TSAs), tumor-associated antigens (TAAs) or neoepitopes. 59 60 TSAs are specific only for tumors. However, many cancers have developed resistance mechanisms to eliminate TSA expression in order to remain hidden from immune surveillance, for example, by downregulating the expression of TSAs and thereby eliminating antigen presentation.…”
Section: Hallmarks Of Immunogenic Cell Death (Icd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Antigens can be tumor-specific antigens (TSAs), tumor-associated antigens (TAAs) or neoepitopes. 59 60 TSAs are specific only for tumors. However, many cancers have developed resistance mechanisms to eliminate TSA expression in order to remain hidden from immune surveillance, for example, by downregulating the expression of TSAs and thereby eliminating antigen presentation.…”
Section: Hallmarks Of Immunogenic Cell Death (Icd)mentioning
confidence: 99%
“…They are mainly proteins that are normally expressed only during embryogenesis or in immune privileged areas such as the brain or gonads. 59 61 Therefore, TAAs are less suitable for ICD-based therapies as the immune cells do not have sufficient specificity for the cancer. On the other hand, neoepitopes arise from mutations in cancer cells and are therefore specific for the tumor.…”
Section: Hallmarks Of Immunogenic Cell Death (Icd)mentioning
confidence: 99%
“…The selection of antigens is a key issue in the establishment and development of cancer vaccines. Various features of antigens, like their immunogenicity and avidity, impact the efficiency of cancer vaccines [171]. The choice of antigen is critical during the design of cancer vaccines to better train and bolster the immune systems of hosts to fight against cancer and eventually eliminate malignant cells.…”
Section: Clinical Trials Of In Vitro Transcription Mrna Vaccines In Melanomamentioning
confidence: 99%
“…Once these antigens are move beyond the testis, a robust immune response against them is aroused. This biological feature endows cancer-germline antigens great potential for use in vaccine design [171,194]. In Wilgenhof's trial, a specific MAGE-A3 and MAGE-C2 immune response was demonstrated in the postvaccination period in 7 and 10 out of 21 patients, respectively.…”
Section: Mrna Vaccines In Melanomamentioning
confidence: 99%
“…As discussed above, altered metabolism is essential in hematologic malignancies to overcome survival stress and adjust to the diverse microenvironment. Thus, therapy against leukemias by targeting reprogramming metabolic molecules seems to be an ideal option to struggle against hematological malignancies and the selection of specific biomarkers is critical in the development of targeted therapeutic agents ( 171 ). Recently, researchers are dedicated to identifying novel metabolism-targeting drugs.…”
Section: Exploiting Of Metabolism Targeting Treatments In Leukemiamentioning
confidence: 99%